2018
DOI: 10.1111/aos.13817
|View full text |Cite
|
Sign up to set email alerts
|

Peripapillary microcirculation in Leber hereditary optic neuropathy

Abstract: Purpose In this prospective observational comparative case series, we aimed to study the peripapillary capillary network with spectral‐domain optical coherence tomography angiography (OCT‐A) in Leber hereditary optic neuropathy (LHON). Methods Twelve eyes of six individuals, of these three males (five eyes) after clinical onset of visual impairment were imaged by OCT‐A with scans centred on optic discs. Control group consisted of 6 eyes with no visual impairment. Results The three affected individuals lost vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 30 publications
0
20
0
2
Order By: Relevance
“…Only 3 studies and a few case reports have quantitatively evaluated the peripapillary or parafoveal microvascular changes in LHON [21-24]. Kousal et al [23] and Balducci et al [21] found that the RPC vessel density in the peripapillary area is reduced in the chronic stage of LHON [21, 23], and Borrelli et al [22] showed that the parafoveal vessel density in the macular area was lower in 29 eyes of LHON patients than in the controls. In the present study, we found that the RGCs (IRT and RNFL) and the retinal vessels supplying the RGCs (SCP and RPC vessel density) were both reduced in patients with chronic-stage LHON compared with those in the controls.…”
Section: Discussionmentioning
confidence: 99%
“…Only 3 studies and a few case reports have quantitatively evaluated the peripapillary or parafoveal microvascular changes in LHON [21-24]. Kousal et al [23] and Balducci et al [21] found that the RPC vessel density in the peripapillary area is reduced in the chronic stage of LHON [21, 23], and Borrelli et al [22] showed that the parafoveal vessel density in the macular area was lower in 29 eyes of LHON patients than in the controls. In the present study, we found that the RGCs (IRT and RNFL) and the retinal vessels supplying the RGCs (SCP and RPC vessel density) were both reduced in patients with chronic-stage LHON compared with those in the controls.…”
Section: Discussionmentioning
confidence: 99%
“…The disease is associated with distinctive abnormalities of peripapillary blood vessels including telangiectatic microangiopathy and small vessel tortuosity [ 109 ]. A prospective multicenter study reported a reduction in vascular blood flow in the temporal sector of the optic nerve in the subacute phase of Leber’s hereditary optic neuropathy, and a reduction in all sectors in the chronic phase [ 110 ]. Borrelli et al showed that eyes with Leber’s hereditary optic neuropathy present SCP and DCP changes that are mainly confined to the nasal and inferior parafoveal sectors corresponding to the papillomacular bundle.…”
Section: Optic Nerve Degenerative Diseasesmentioning
confidence: 99%
“…This amelioration of the reprogramming efficiency is relevant not only to obtain enough biological material for further investigations but could also unravel an insight into pathogenic mechanisms, relevant for the disease, and for the development of targeted effective therapy. Remarkably, the subacute phase of LHON is hallmarked by well-known vascular changes, and ongoing discussions revolve around the issue of pseudo-hypoxic signaling that RGCs may produce as their metabolic unbalance reaches the threshold for triggering the disease, possibly underlying the microangiopathy in LHON ( 3 , 4 , 47 , 48 ).…”
Section: Reprogramming Fibroblasts or Peripheral Blood Mononuclear Cells Pbmcs From Lhon Patientsmentioning
confidence: 99%